Corpos trans e os lugares que (não) podem ocupar: o discurso de Linn da Quebrada e a produção de sentidos na cidade - Pagnan, Redson (2019)
This dissertation proposes to discuss relations between gender and urban space, based on Linn da Quebrada's intersemiotic discursive practice, in order to (re) think the forms of gender identity construction from the deconstruction of cisheteronormativity, given as natural . It also aims to reflect on the marginal places in which deviant bodies are compulsorily placed, but which, however, do not consolidate as spaces of living fully. Bodies that flee to naturalized patterns of gender and sexuality live in transit, between center and periphery, between places and non-places, that is, in most cases, occupy spaces of anonymity and the impossibility of building lasting affections. Thus, the city center becomes a space of passage, where they can experience some aspects of their sexuality and varied gender performances, but it is not possible for them to live fully there. Also the peripheries do not accept them as they are. Linn da Quebrada assumes a place of subject in process, a body that claims its existence and other people like it through a hyperbolic aesthetic, which uses elements hitherto considered as signs of fragility, to build a body that transgresses the cisheteronorms. This dissertation focuses on a corpus composed of: i) songs and video clips; ii) album or single cover; iii) film or documentary and iv) interview video; chosen as exemplars of the discursive production of the canonical music space and associated space of the artist (Corning, MAINGUENEAU, 2009). For the analysis, I use the theoretical and methodological framework of French Line Discourse Analysis, reflections on the relationship between the body and the city coming from Philosophy, Sociology and Architecture, as well as the assumptions of the Queer studies. The latter offer ways of thinking about gender and sexuality beyond the heteronormative perspective and the historically and discursively constructed binarisms that guide (perform) the subjects' practices, including in the field of architecture. The work of analysis allows us to understand the ways in which Linn da Quebrada's discursive practice makes an ethos emerge, an image of enunciator that cries out for the marginalized bodies and their rights to a place in the excluding city, a city that is a place to live and not a place of permanent transit. It is hoped, with this research, to contribute to the expansion, in the field of Architecture and Urbanism, the discussions about the organization of the cities, so that they can be more inclusive. It is also sought some contribution in the theoretical field of Discourse Analysis, postulating that the concepts proposed by Maingueneau (2009) for the study of the literary phenomenon can be applied to analyze materialities of other fields of artistic making, such as, in the case of this dissertation, the literomusical.